Intestinal and Tissue Parasites and their Relation with Eosinophilia in a Yukpa Amerindian Community from the Mountains of Perijá, State of Zulia - O. Suárez Díaz; A. Atencio; M. Carruyo; P. Fernández; R. Villalobos; Z. Rivero; A. Maldonado; A. Bracho; A. Ruiz; M. González; O. Briceño; M. Quintero; et al. (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2013)
To determine the prevalence of intestinal and tissue parasites and their relationship with eosinophilia in Yukpa Amerindians, 91 fecal and blood samples were analyzed. The fecal samples underwent microscopic and concentrated examinations. Complete hematology was performed to determine white count and percentage of eosinophils; and ELISA tests were performed on the serum to detect anti-Toxocara canis and anti-Toxoplasma gondii antibodies. A high prevalence of intestinal parasites (90.10%) was observed. The predominance of protozoa over helminths was noted; for the first, the most prevalent were Blastocystis hominis (51.64%), and for the second, Ascaris lumbricoides (38.46%). Seroprevalence of anti-Toxocara canis antibodies was 24.17% and for anti-Toxoplasma gondi, 43.95%. No statistically significant differences were observed between age and sex groups for the different intestinal and tissue parasites. No association between seroprevalence for Toxocara canis and eosinophilia was found. A statistically significant association between the presence of eosinophilia and helminthiasis was observed. These results suggest that there is a high prevalence of parasitic infections in these communities due probably to their customs and the sanitary conditions in which they live.